Quality of career indicators for Umm Al-Qura University employees - Kholood Alyousef (Umm Al-Qura University, 2022)
The study aimed to reveal the quality of life of Umm Al-Qura University employees, and the quality of life in good grades, and reaching good, and considering the quality of life among Umm Al-Qura University employees, and used the descrip-tive approach, and the guest house as a tool, where the questionnaire distributed a random sample Of the employees, male and female employees of an organization, or male and female employees, male and female employees, among them (95) a questionnaire. The study reached the following results: The availability of quality indicators of job life for Umm Al-Qura University employees came to a medium degree at a rate of (65%), and in the order of its dimensions: First place in the dimension of human relations and effective communications with a percentage of (71%), The second place comes after participation in decision-making and delegation of powers by (65%), and in the same order came the dimension of the physical, moral and health environment, The third rank came after job stability and security with a rate of (62%), and in the same rank came after work conditions and financial benefits, The most prominent obstacles to the quality of job life among Umm Al-Qura University employees were according to the weighted average (210.7) and the relative strength (44.4%). The study found suggested indicators to improve the quality of career life for Umm Al-Qura University employees.